Development of a collagen-like peptide polymer via end-to-end disulfide cross-linking and its application as a biomaterial. (August 2019) - Ichise, Shinichiro F.; Takeuchi, Shungo; Aoki, Shigehisa; Kuroda, Kazuki C.; Nose, Hiroshi; Masuda, Ryo; Koide, Takaki
Graphical abstract: Abstract: Collagen is the most abundant protein in the animal kingdom and has a unique triple-helical structure. It not only provides mechanical strength to tissues, but also performs specific biological functions as a multifaceted signaling molecule. Animal-derived collagen is therefore widely used as a biocompatible material in vitro and in vivo . In this study, we developed a novel peptide-based material that mimicked both the polymeric properties and a selected biological function of native collagen. This material was prepared by end-to-end multiple disulfide cross-linking of chemically synthesized triple-helical peptides. The peptide polymer showed a gel-forming property, and receptor-specific cell binding was observed in vitro by incorporating a peptide harboring an integrin α2β1-binding sequence. Furthermore, cell signaling activity and biodegradability were tunable according to the polymer contents. The results demonstrated the potential of this material as a designer collagen. Statement of Significance: Collagen is a useful biomaterial with the gel-forming property. It also exhibits various biological activities through the interaction of specific amino acid sequences displayed on the triple helix with functional biomacromolecules. Here we report a novel synthetic material, artificial collagen, by end-to-end cross-linking of chemically synthesized collagen-like triple-helical peptides. The material allows independent regulation of polymer properties, i.e. gel stiffness, and sequence-specific bioactivities by altering peptide compositions. This material can also be variously shaped, for example, thin films with high transparency. In addition, it has low inflamatogenic properties and tunable biodegradability in vivo .